Intention and Pedagogical Competence: Use of Collaborative Learning in the Subject of Mathematics in Secondary School - Gómez, Luis F. (2016)
This review analyzes the experience reported by teachers of mathematics in public junior high schools in Jalisco, México, about the collaborative work of students to learn mathematical content and processes. Weekly logs of 30 teachers were analyzed during one school year to identify modalities of collaborative work, contents or processes taught in this way, evaluative comments about this modality of work to achieve learning and the decisions made by teachers after evaluating its efficacy. It was found that all teachers promoted collaborative work but with varied frequency and in different ways, mainly to solve problems, for discovery activities, to generate hypotheses and to extract information from given information. Drawing from their experience, teachers made different evaluations about collaborative learning and consequently they took the decision to continue promoting it or decrease it and in the latter case increase the direct teaching and individual work of students. It is concluded that teachers try to promote learning through collaboration, but lacked the pedagogical competence required to do it, so not all of them had the results they expect, so some of them return to teach through direct teaching, giving explanations and writing demonstrations on the blackboard.